REPRESENTASI PERAN EKSISTENSI PEREMPUAN DALAM NOVEL PEREMPUAN PANGGUNG KARYA IMAN BUDHI SANTOSA - Dita Nurlita; Siti Fatimah; Pipit Mugi Handayani (Universitas Negeri Makassar, 2024)
This research aims to describe the existence of women in the novel Perempuan Panggung by Iman Budhi Santosa, using Simone de Beauvoir's theory. This research is descriptive and qualitative. The data for this research are quotations that contain representations of the role of women's existence. The data source for this research is the novel Perempuan Panggung by Iman Budhi Santosa. The results of this research are four forms of women's existence strategies, including: representation of women working, representation of intellectual women, representation of women's social transformation of society, and representation of women rejecting their queerness.